Manajemen Sumber Daya Insani (Persepsi Dasar Perencanaan Dan Analisis Jabatan Di Perbankan Syariah) - Sitorus, Eva Afrilisa; Aslami, Nuri (Jurnal Manajemen Akuntansi (JUMSI), 2024)
In the age of globalization, numerous obstacles arise in the face of worldwide competition. One such challenge is the unrestricted, free competition present in specific regions and nations. This liberty to conduct business has become a necessity for the international community in every aspect. Thus, the significance of Human Resource Management (MSDI) cannot be overstated for Islamic Banks. It is vital to manage and utilize human resources in a productive, effective, and efficient manner to survive and thrive in the international arena.  Human resources are an inexhaustible bounty from Allah SWT. However, if they are not appropriately managed, organizations, businesses, and even nations can fall behind and crumble. If an organization, company, or country fails to develop, the problem lies not with the quality of human resources, but with the quality of human resource management. Proper management can bring out the best in people and lead to the growth of institutions, companies, and developed countries. To achieve this objective, the workforce is meticulously planned and comprehensively analyzed in terms of positions (jobs) within the SDI section of the Shariah Bank. This is done to identify qualified candidates and bring them together in one place.